On the validity of dark matter effective theory - Bauer, Martin; Butter, Anja; Desai, Nishita; González Fraile, Juan; Plehn, Tilman (Arxiv, 2017)
An effective theory of dark matter offers an attractive framework for global analyses of dark matter. In the light of global fits we test the validity of the link between the non-relativistic dark matter annihilation, or the predicted relic density, and LHC signatures. Specifically, we study how well the effective theory describes the main features of simple models with s-channel and t-channel mediators coupling to the Standard Model at tree level or through one-loop diagrams. Our results indicate that global dark matter analyses in terms of effective Lagrangians are highly non-trivial to interpret in term of actual models.
Published online: 29 Nov 2016
Gesehen am 11.08.2017